Morigerando las costumbres. Canalizando las disputas. A propósito de los conflictos en los pueblos heredianos. 1885-1915 - Gil Zúñiga, José Daniel (2001)
Explains why fewer homicides took place in villages in the province Heredia, between 1885 y 1915, although there were frequently intercomunal conflicts.